2019
DOI: 10.1371/journal.pbio.3000559
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm displays rapid responses to diet

Abstract: The global rise in obesity and steady decline in sperm quality are two alarming trends that have emerged during recent decades. In parallel, evidence from model organisms shows that paternal diet can affect offspring metabolic health in a process involving sperm tRNAderived small RNA (tsRNA). Here, we report that human sperm are acutely sensitive to nutrient flux, both in terms of sperm motility and changes in sperm tsRNA. Over the course of a 2-week diet intervention, in which we first introduced a healthy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
162
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(191 citation statements)
references
References 74 publications
19
162
0
1
Order By: Relevance
“…, outlines the main functions of sperm RNA types in spermatogenesis and SPZ). [78] rsRNAs Mature SPZ are enriched in rsRNAs [50] rsRNAs are considered sperm quality biomarkers [49] Small RNA profiles in ejaculated sperm, epididymal sperm and seminal plasma indicate that sperm RNAs may have origins other than the testes [79] The deletion of a mouse tRNA methyltransferase, DNMT2, abolisheds sperm sncRNA-mediated transmission of high-fat diet (HFD)-induced metabolic disorders to offspring [80] Since SPZ are transcriptionally and translationally silent cells before departing the testes [81], it is plausible that the substantial remodeling of their ncRNA cargo may be driven extrinsically along the epididymis, a long convoluted tubule connecting rete testis to the vas deferens, composed of three main anatomical regions (caput, corpus and cauda), with a considerable segment to segment variation. Leading candidates to promote this crosstalk are epididymal epithelial cells that communicate with SPZ through epididymosomes, vesicles-heterogeneous in their lipid/protein/RNA composition and density-released through an apocrine secretory mechanism [82].…”
Section: Sperm Rna Codementioning
confidence: 99%
“…, outlines the main functions of sperm RNA types in spermatogenesis and SPZ). [78] rsRNAs Mature SPZ are enriched in rsRNAs [50] rsRNAs are considered sperm quality biomarkers [49] Small RNA profiles in ejaculated sperm, epididymal sperm and seminal plasma indicate that sperm RNAs may have origins other than the testes [79] The deletion of a mouse tRNA methyltransferase, DNMT2, abolisheds sperm sncRNA-mediated transmission of high-fat diet (HFD)-induced metabolic disorders to offspring [80] Since SPZ are transcriptionally and translationally silent cells before departing the testes [81], it is plausible that the substantial remodeling of their ncRNA cargo may be driven extrinsically along the epididymis, a long convoluted tubule connecting rete testis to the vas deferens, composed of three main anatomical regions (caput, corpus and cauda), with a considerable segment to segment variation. Leading candidates to promote this crosstalk are epididymal epithelial cells that communicate with SPZ through epididymosomes, vesicles-heterogeneous in their lipid/protein/RNA composition and density-released through an apocrine secretory mechanism [82].…”
Section: Sperm Rna Codementioning
confidence: 99%
“…This study further revealed that Dnmt2-mediated m 5 C affected the secondary structure and biological properties of abundant 3ʹ-tRFs upon transfection in cell lines [46], although the exact contribution of m 5 C for tRF-mediated paternal inheritance was not fully delineated. Similarly, a recent study in humans showed that i-tRF levels in sperm cells from healthy donors were dynamically modulated in response to acute diet intervention and were positively associated with increased sperm motility [48]. Hence, further studies will be required to qualitatively assess the function of tRFs during the early developmental stages and their contribution to the transmission of paternally acquired metabolic traits.…”
Section: Trfs In Epigenetic Regulation and Germline-mediated Intergenmentioning
confidence: 99%
“…Therefore, the study raised a very intriguing question of whether tsRNAs induced by cardiac hypertrophy could be inherited by the next generation and lead to pathogenesis. In fact, there are several lines of evidence consistently indicating that tsRNAs are enriched in sperm (Chen et al, 2016;Sharma et al, 2016;Natt et al, 2019;Sarker et al, 2019;Zhang et al, 2019). Some studies demonstrated the intergenerational inheritance of tsRNAs by injecting tsRNAs from the sperm of males fed a high fat diet into normal zygotes, and showed the offspring had altered expression of metabolic pathway components in addition to developing a metabolic disorder (Chen et al, 2016;Sarker et al, 2019).…”
Section: Role Of Transfer Rna-derived Small Rnas In Cardiac Hypertrophymentioning
confidence: 99%